Diagnostic Accuracy of Transvaginal Ultrasound (TVS) in Diagnosing Müllerian Duct Anomalies Keeping Magnetic Resonance Imaging (MRI) as Gold Standard - Kumari, Monika; Ahmed, Adnan; Jatoi, Asma; Channa, Soonh; Majeed, Bushra (Indus Journal of Bioscience Research, 2025)
Objective: To determine the diagnostic accuracy of transvaginal ultrasound in diagnosing Müllerian duct anomalies by using magnetic resonance imaging as the gold standard. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was conducted from 2 March 2025 to 2 June 2025 at the Department of Radiology, Liaquat University of Medical and Health Sciences, Jamshoro. Methodology: A total of 348 female patients aged 20–45 years presenting with pelvic pain or infertility were included. All patients underwent transvaginal ultrasound followed by magnetic resonance imaging of the pelvis. Findings of both imaging modalities were recorded separately. Magnetic resonance imaging was taken as the reference standard. Data were analyzed using Statistical Package for Social Sciences version 22. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of transvaginal ultrasound were calculated using a 2 × 2 contingency table. Results: The mean age of patients was 32.16 ± 7.64 years, and the mean duration of symptoms was 24.46 ± 13.81 months. Transvaginal ultrasound detected Müllerian duct anomalies in 24.7% patients, while magnetic resonance imaging confirmed anomalies in 14.9% patients. Sensitivity of transvaginal ultrasound was 50%, specificity was 79.70%, and overall diagnostic accuracy was 75.30%. Conclusion: Transvaginal ultrasound shows moderate diagnostic accuracy in detecting Müllerian duct anomalies.